Thrombotic and hemorrhagic complications in children and young adult recipients of Hematopoietic Stem Cell Transplant (HSCT). Issue 167 (July 2018) - Kaur, Dominder; Ashrani, Aneel A.; Pruthi, Rajiv; Khan, Shakila P.; Bailey, Kent; Rodriguez, Vilmarie
Abstract: Background: Overall incidence of hemostatic complications in pediatric recipients of Hematopoietic Stem Cell Transplant (HSCT) is scarcely studied. This retrospective review explored the incidence and underlying risk factors of bleeding and thrombotic complications in children. Procedure: Clinical characteristics, hemorrhagic events (HE), thrombotic events (TE) and follow up data were abstracted from medical records on patients aged <21 years undergoing HSCT during January 2000–June 2015. Results: From start of conditioning until last follow up, 238 pediatric patients were reviewed during this study. There were 16 symptomatic thrombotic complications in 15 patients, along with 13 major bleeding events. Incidence of HE or TE was higher in allogeneic HSCT compared to autologous HSCT ( p  = 0.02). Severe thrombocytopenia could not be identified as a major contributor to bleeding. All patients with HE had platelets between 20, 000–50, 000 × 10 9 /L, except one patient, who had platelets <20, 000 × 10 9 /L. All patients with hemorrhagic cystitis ( n  = 7) had received cyclophosphamide (Cy). For patients with sinusoidal obstruction syndrome, conditioning included either busulfan (Bu)/Cy ( n  = 5), Cy with total body irradiation ( n  = 4), or thiotepa ( n  = 2). Among allogeneic HSCT recipients, 60% of HE and 92% with TE had underlying myeloid neoplasms. Graft versus Host disease contributed to both types of complications ( p  = 0.07), although not reaching statistical significance. Conclusions: Allogeneic pediatric HSCT patients had higher overall risk of hemorrhagic or thrombotic complications compared to autologous recipients in this study. HSCT for myeloid malignancies was a risk factor for higher complications. Highlights: Incidence of hemostatic complications was 5.5% in the autologous HSCT recipients in this study and 14.7% in the allogeneic group. Hemorrhagic cystitis associated bleeding, and sinusoidal obstructive syndrome, were the main bleeding and thrombotic events in this study. Myeloid malignancy related indication for HSCT was a significant risk factor for both hemorrhagic and thrombotic complications. The age distribution of events is described in this study, and a very high incidence of complications was noted in the five infants that underwent HSCT. Overwhelming majority of hemostatic events noted in this study were complications unique to HSCT recipients. Other complications such as catheter associated thromboses were overall low in our patient population.